Clinical Profile of Patients Attended in Obstetrics and Gynaecology Outpatient Department of Marine City Medical College Hospital, Chattogram (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Prevalent Disease: The number of cases of a disease, number of infected people or number of people with same other attribute present during a particular interval of time. The objective of this study to see the prevalent diseases among the patients attended in Gynae OPD of Marine City Medical College Hospital.Materials and methods: This cross-sectional descriptive study included all patients attended in OPD of Marine City Medical College Hospital during the year 2024. Patient’s data were taken from hospital registration books.Results: Among a total of 24,985 outdoor patient attended in this institute during the study period, 3045 (12.2%) attended in Gynaecological and Obstetrics OPD. Among them, majority (65.3%) were obstetrics patients. Married women were 2932 (96.3%) and unmarried were 1113 (3.7%). Among them 89.3% came for antenatal checkup and 10.7% for postnatal checkup. Gynaecological most common cases were Abortion184 (17.4%) Vaginal discharge 179(17%) and AUB 151(14.3%). Conclusion: The major bulk of the patients were obstetric patients attended for antenatal care. Increasing awareness among people in this area will increase access to medical services.    JCMCTA 2025 ; 36 (1) : 102-106